RONC-10. OUTCOMES OF STEREOTACTIC RADIOSURGERY FOR PILOCYTIC ASTROCYTOMA: AN INTERNATIONAL MULTICENTER STUDY. Issue 2 (22nd June 2018) - Murphy, Erin S; Sheehan, Jason P; Trifiletti, Daniel M; Mathieu, David; Kano, Hideyuki; Fang, Fang; Lee, John Y K; McShane, Brendan; Lee, Cheng-chia; Yang, Huai-che; Alvarez, Roberto Martinez; Moreno, Nuria Martinez; et al.
Abstract: BACKGROUND: The utility of radiosurgery is not well documented for pilocytic astrocytoma. We analyzed the efficacy and prognostic factors associated with Gamma Knife radiosurgery (GKRS) for pilocytic astrocytoma in an international multicenter trial. METHODS: Nine medical centers from the International Gamma Knife Research Foundation provided data. Patients treated with single session GKRS with histologic diagnosis of pilocytic astrocytoma were eligible. Patient, tumor, and treatment variables were analyzed. RESULTS: 141 patients with a median age 13.9 years (range: 2-84) were included. Median follow up was 67.3 months. Twenty-one (15%) had radiotherapy (RT) and 11 (8%) had chemotherapy prior to GKRS. Median margin dose: 14 Gy (range: 4-22.5). Median tumor volume:3.45cc (range: 0.17-33.7). Overall survival at 3, 5 and 10 years from GKRS was 96.8%, 95.7% and 92.5%, respectively. Thirty-four patients progressed resulting in progression-free survival (PFS) at 3, 5, and 10 years of 80.8%, 74.0%, and 69.7%, respectively. For patients <18 years old, 3, 5, and 10 year PFS was 88.3%, 81.3%, and 77.0%, respectively. This was significantly improved (p=0.008) compared to patients ≥18 years old (3, 5, and 10 year PFS of 67.3%, 60.9%, and 56.8%, respectively). Similarly, patients without prior RT (p=0.001), or prior chemotherapy (p=0.003), and with tumor volume <4.5cc (p=0.012) had significantly better PFS. On multivariable analysis, only prior RT impacted PFS (p=0.001, HR=3.705, CI: 1.76-7.80). CONCLUSIONS: GKRS for pilocytic astrocytoma results in excellent long term survival and good local control. GKRS may be a particularly useful minimally invasive tool for younger patients with smaller tumor volumes.